Liquid biphasic flotation system (LBFS) for separation of protein from Azolla pinnata - Kobbin, Kiishhen; Peter, Angela Paul; Mohd Nor, Mohd Zuhair; Show, Pau Loke (Universiti Putra Malaysia Press, 2025)
The demand for plant-based protein has surged as consumers nowadays are highly conscious about their daily intake; thus, this has driven extensive research on plant-based protein. Industries are now focusing on minimal operational costs while being environmentally friendly. This project specifically targets the extraction of protein from Azolla pinnata using a liquid biphasic flotation system (LBFS). LBFS is a promising extraction method incorporating microbubbles to enhance protein separation efficiency in liquid-liquid extraction. The LBFS processing parameters are the type of solvent (ethanol and 2-propanol), solvent concentration (75-100%), salt concentration (200500 g/L), biomass load (100-400 mg), and flotation time (5-15 min). The study's findings revealed that 2-propanol, with its polarity, yielded the highest protein recovery and separation efficiency. Increasing the solvent concentration led to a higher yield of extracted protein due to the greater number of hydroxyl groups per unit volume. Higher salt concentrations aid the separation process by enhancing hydrophobic contact between the protein and water. A higher biomass load resulted in greater protein recovery, while a longer flotation duration improved protein extraction due to lower particle surface tension. However, vigorous flotation conditions could lead to protein degradation. Based on the study's optimisation, the LBFS conditions that yielded the best results were 80% 2-propanol solvent, 400 g/L salt concentration, 300 mg biomass load, and a flotation time of 10 min. These conditions resulted in a protein yield recovery of 78.19% ±4.31 and a protein separation efficiency of 79.39% ±2.80. This method provides a high protein yield recovery and separation efficiency for the extraction of biomolecules.